Numerical simulation of a novel small water turbine generator for installation in a deep-flow hydroponics system - Werayoot Lahamornchaiyakul (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
Hydroponics systems are crucial for providing sustainable and cost-effective choices when soils are unavailable for conventional farming. The application of water flow rates within hydroponics systems to generate electricity is another idea that can be used in the field of power generation. This paper presents the determination of the mechanical power efficiency of a novel small water turbine generator for use in a deep-flow hydroponics system (DFT). The system was designed, analysed, and calculated for the most suitable geometries of the water pipeline inlet, DFT system, main structure of the PVC Tee Pipe Fitting, and a water turbine wheel using computational fluid dynamics software. The diameter of the water turbine wheel in this research was 48 mm. A DFT hydroponic system was modelled for the purposes of this research. We conducted a numerical simulation with water flow rates of 6, 8, and 10 l/min to evaluate the turbulent kinetic energy distribution in the DFT hydroponic system. The numerical simulation employed the control volume methodology, and the k-epsilon turbulence model was applied to obtain the computational conclusions. The highest torque and power that a novel small water turbine for installation in a DFT system could generate at a maximum flow rate of 0.000167 m3/s were 0.082 N.m. and 1.9568 watts, respectively. The forces generated by the fluid's speed and pressure can then be transferred to the building process of a novel small water turbine wheel. The FEA numerical result shows that the maximum value of the total deformation at a wheel speed of 228 rpm is 7.0 x 10-5 mm. The numerical simulations used in this study could potentially be used to further develop prototypes for innovative miniature water turbines that generate commercial electricity.